2010
DOI: 10.1111/j.1740-8261.2010.01693.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Technical Quality Assessment of Hip-Extended Radiographs on Interobserver Agreement in the Diagnosis of Canine Hip Dysplasia

Abstract: Experienced and inexperienced observers evaluated the assessability of 50 radiographs (25 dogs) and determined the hip status (dysplasia/nondysplasia and final scoring according Fe´de´ration Cynologique Internationale [FCI]-criteria) individually. A radiographic technical quality assessment was performed in a separate reading session. Interobserver agreement in determining dysplasia/nondysplasia and FCI-scoring did not significantly increase with the increasing quality of a radiograph, irrespective whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
3
13
0
1
Order By: Relevance
“…From these, 50 radiographs were selected to represent the reported relative frequency of FCI (Féderation Cynologique Internationale) scores: 28% A, 36% B, 24% C, 8% D, and 4% E . The selected radiographs met technical and positional requirements described in a previous study, which comply with the official screening regulations of the FCI. Furthermore, selection was based on the presence of a CFHO, CCO, osteosclerosis of the CrAE, and DJD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From these, 50 radiographs were selected to represent the reported relative frequency of FCI (Féderation Cynologique Internationale) scores: 28% A, 36% B, 24% C, 8% D, and 4% E . The selected radiographs met technical and positional requirements described in a previous study, which comply with the official screening regulations of the FCI. Furthermore, selection was based on the presence of a CFHO, CCO, osteosclerosis of the CrAE, and DJD.…”
Section: Methodsmentioning
confidence: 99%
“…Radiographic assessment of canine hip joints has been used for over 4 decades in several screening mechanisms worldwide. Several authors reported low inter‐ and intraobserver agreement of subjective hip scoring of the ventrodorsal hip extended radiographic view . Changes in hip joint phenotype can manifest themselves as hip joint remodeling, hip joint laxity, and degenerative joint disease (DJD).…”
mentioning
confidence: 99%
“…Hip dysplasia can affect more than 40% of dogs of various breeds (Comhaire et al 2009;Ginja et al 2009) and the progress made in decreasing the incidence of canine HD remains low (Verhoeven et al 2010;Smith et al 2012). Accurate screening for canine HD is essential to make adequate recommendations regarding breeding programmes (Chalmers et al 2013) and treatment of canine HD (Verhoeven et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Accurate screening for canine HD is essential to make adequate recommendations regarding breeding programmes (Chalmers et al 2013) and treatment of canine HD (Verhoeven et al 2010). Radiographic assessment and measurements on the standard VDHE view are the basis of the main international HD scor- Veterinarni Medicina, 62, 2017 (07): 377-385 doi: 10.17221/127/2016-VETMED ing systems: FCI, OFA and BVA/KC (Genevois et al 2007;Skurkova et al 2010;Chalmers et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Standard pelvic radiographs have a low sensitivity for diagnosing HD in juvenile dogs prior to the development of degenerative changes in the hip joints. 1,2 In contrast to the subjective evaluation typically performed to evaluate standard pelvic radiographs, distraction view radiographs are obtained while applying tension to the ligament of insertion of the femoral head and joint capsule and allow objective quantitation of hip joint laxity. 3 Distraction view pelvic radiographs allow calculation of a distraction index (DI), which quantitates the relative degree of lateral femoral head displacement from the acetabulum.…”
Section: Introductionmentioning
confidence: 99%